2016
DOI: 10.1017/s1751731115002025
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between efficiency of nitrogen utilization and isotopic nitrogen fractionation in dairy cows: contribution of digestion v. metabolism?

Abstract: Animal tissues are naturally 15 N enriched relative to their diet and the extent of this difference (Δ 15 N animal-diet ) has been correlated to the efficiency of N assimilation in different species. The rationale is that transamination and deamination enzymes, involved in amino acid metabolism are likely to preferentially convert amino groups containing 14 N over 15 N. However, in ruminants the contribution of rumen bacterial metabolism relative to animal tissues metabolism to naturally enrich animal proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
31
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 39 publications
10
31
3
Order By: Relevance
“…This correlation was reduced to 28.7% (P < 0.001) when excluding the effect of dietary additive. The general form of this relationship is commonly observed across different species and breeds of ruminants 4 , 5 , indicating the potential of Δ 15 N animal-diet as a biomarker for FCE. Previous work has shown that a significant proportion of N isotopic discrimination results from processes involved in N metabolism – particularly in the liver 1 , 2 , and rumen microbial metabolism 3 .…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…This correlation was reduced to 28.7% (P < 0.001) when excluding the effect of dietary additive. The general form of this relationship is commonly observed across different species and breeds of ruminants 4 , 5 , indicating the potential of Δ 15 N animal-diet as a biomarker for FCE. Previous work has shown that a significant proportion of N isotopic discrimination results from processes involved in N metabolism – particularly in the liver 1 , 2 , and rumen microbial metabolism 3 .…”
Section: Resultsmentioning
confidence: 85%
“…At the mechanistic level, differences in the rates of biochemical reactions causing N isotopic discrimination contribute to the overall observed discrimination (Δ 15 N). Previous studies have reported negative relationships between FCE and Δ 15 N 4 , 5 , suggesting that the relationship with FCE may stem from its strong association with N intake and growth, thus reflecting the incorporation of N into tissue versus its excretion in urine 6 – hence current interest in estimating the composition of gain.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in the present data set, the correlation between predicted milk urea and NUE was only −0.3. Other works have predicted NUE from 15 N fractions in tissues (Cheng et al, 2011;Cantalapiedra-Hijar et al, 2016) but either resulted in models with low R 2 or concluded Grelet et al: MIR PREDICTION OF NITROGEN EFFICIENCY Figure 2. Plot of measured individual nitrogen use efficiency (NUE) of dairy cows compared with NUE values predicted by the support vector machines regression (SVM) model using mid-infrared (MIR) spectra, parity, and milk yield as predictors, in cross-validation with 10 subsets (n = 1,034).…”
Section: Mir Modelsmentioning
confidence: 99%
“…Methods based on N isotopes have also been investigated. Although Cantalapiedra-Hijar et al (2016) obtained a model predicting NUE with a coefficient of determination (R 2 ) of 0.5, Cheng et al (2011) were unable to validate the link between 15 N isotopic fractionation and NUE for the diets used in their experiments. According to Herremans et al (2019), the 15 N isotopic fractionation method would be more appropriate for estimating urinary nitrogen excretion than overall N use efficiency.…”
Section: Introductionmentioning
confidence: 97%
“…In ruminants, the natural 15 N enrichment of animal proteins over the diet has been proposed as a proxy for N use efficiency (Cantalapiedra-Hijar et al, 2018). The contribution of rumen microbiota to this link has been acknowledged (Cantalapiedra-Hijar et al, 2016) but the underlying mechanism remains unknown. Based on previous studies we hypothesized that the N isotopic signature of rumen bacteria (Δ 15 N bacteria-substrate ) depends on the balance between uptake and release of ammonia (Martinez-Fernandez et al, 2018), both reactions being catalysed by enzymes discriminating against 15 N. Because rumen bacteria differ in their N metabolism it is expected that Δ 15 N bacteria-substrate would reflect their prevailing ability to assimilate or release ammonia.…”
Section: Introductionmentioning
confidence: 99%